Has it become a trend? Characteristics and strategies of fashion events in Brazil - de Lima Claudino, Adson; Lanzarini, Ricardo (Tourism and Hospitality International Journal, 2024)
Fashion events are authentic and creative events that promote trends and innovations in the fashion chain, disseminate knowledge about the area, radiate benefits to other markets, contribute to the marketing of the destinations that host them, and stimulate consumer behavior through desire. Given this scenario, the aim of this study was to identify the characteristics and strategies of fashion events held in Brazil, revealing their purposes and contributions to localities and tourism. To this end, a descriptive and exploratory phenomenological study with a qualitative approach was used, with data collected through interviews via the Google Meet platform with professionals linked to the fashion events market across the country. The data was systematized and analyzed using Iramuteq software (version 0.7 alpha 2). The results showed the commercial and artistic nature of these events, which encourage the appreciation of Brazilian culture and regional identity, and have the potential to consolidate tourism segments in this area. The research intends that companies and government bodies can recognize the relevance of the segment for the economy, for cultural appreciation and as a tourism enhancer, so that they invest in its activities.